2019
DOI: 10.1177/1049909119895496
|View full text |Cite
|
Sign up to set email alerts
|

Experiences at the End of Life From the Perspective of Bereaved Parents: Results of a Qualitative Focus Group Study

Abstract: Background: Palliative care principles are known to support the experiences of children and their families throughout the illness trajectory. However, there is little knowledge of the parental perceptions of care delivered and gaps experienced by families receiving end-of-life care. We report the most helpful aspects of care provided during the end of life and identify opportunities to improve care delivery during this critical time. Methods: This study consists of 2 one-hour focus group sessions with 6 partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(42 citation statements)
references
References 24 publications
(29 reference statements)
0
42
0
Order By: Relevance
“…However, they are all services that parents participated in the previous focus groups identified as lacking. 13 Consistent with the focus groups' perspective, parents who returned the mailed survey reported that they thought that services would be helpful at a much higher rate than they reported utilizing those services. For example, 16 parents reported that a cancer support group for parents would be "very helpful" or "somewhat helpful" and 15 parents reported that mental health resources for parents would be "very helpful" or somewhat helpful".…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, they are all services that parents participated in the previous focus groups identified as lacking. 13 Consistent with the focus groups' perspective, parents who returned the mailed survey reported that they thought that services would be helpful at a much higher rate than they reported utilizing those services. For example, 16 parents reported that a cancer support group for parents would be "very helpful" or "somewhat helpful" and 15 parents reported that mental health resources for parents would be "very helpful" or somewhat helpful".…”
Section: Discussionmentioning
confidence: 80%
“…The survey was developed by the study team based on results from focus group discussions. 13 The study team included pediatric oncology physicians, a pediatric bone marrow transplant nurse practitioner, a pediatric palliative care physician, a pediatric psychologist with experience in palliative care, and a medical student. The focus groups discussed what went well, what did not go well, and suggested improvements for end-of-life care.…”
Section: Methodsmentioning
confidence: 99%
“…Exacerbation of parental grief [ 10 , 146 ] was also noted when the child experienced poor symptom management [ 10 , 108 , 143 , 146 , 151 , 152 ], prolonged illness [ 120 ], and a hospital death [ 162 ], particularly when the parent was separated from the child [ 131 , 148 ], insufficiently prepared for the loss [ 92 , 100 , 113 , 116 , 131 , 150 , 163 ], and faced a lack of conducive environment to say goodbye [ 148 , 164 ]. Psychosocial morbidities were exacerbated by poor transition of care [ 114 , 127 , 129 , 140 , 143 , 148 ], poor communication [ 10 , 82 , 116 , 117 , 129 , 131 , 132 , 135 , 143 , 148 , 165 – 167 ], unrealistic prognostication [ 10 , 113 , 129 , 132 , 135 , 138 , 165 , 166 ], role conflict between parents and healthcare providers during end of life decision making [ 167 – 169 ] and the healthcare providers’ lack of cultural sensitivity [ 170 ]. Anger, fear and guilt [ 96 , 106 , 117 , 118 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Psychosocial morbidities were exacerbated by poor transition of care [ 114 , 127 , 129 , 140 , 143 , 148 ], poor communication [ 10 , 82 , 116 , 117 , 129 , 131 , 132 , 135 , 143 , 148 , 165 – 167 ], unrealistic prognostication [ 10 , 113 , 129 , 132 , 135 , 138 , 165 , 166 ], role conflict between parents and healthcare providers during end of life decision making [ 167 – 169 ] and the healthcare providers’ lack of cultural sensitivity [ 170 ]. Anger, fear and guilt [ 96 , 106 , 117 , 118 , 134 , 163 , 171 ], anxiety, depression, post-traumatic stress symptoms [ 89 , 158 , 163 , 168 , 172 , 173 ], insomnia [ 89 ], permanently damaged parental self-concept [ 168 ], role confusion [ 171 ], poor social function [ 10 , 89 , 99 ], functional impairment such as phobias or somatic problems [ 81 , 92 , 155 , 163 , 174 ], suicidal ideation and prolonged grief [ 10 , 89 ] were also exacerbated by inadequate soc...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation